Post-COVID-19 Fatigue and SARS-CoV-2 Specific Humoral and T-Cell Responses in Male and Female Outpatients - Meisinger, Christa; Goßlau, Yvonne; Warm, Tobias D.; Leone, Vincenza; Hyhlik-Dürr, Alexander; Linseisen, Jakob; Kirchberger, Inge (Frontiers in Immunology, 2022)
Background Information on the clinical characteristics and pathophysiological mechanisms underlying post-COVID-19 fatigue are scarce. The main objective of this study was to evaluate sex-specific humoral and T-cell responses associated with post-COVID-19 fatigue in a sample of individuals treated as outpatients. Methods At a median time of 277 (183;323) days after the acute infection, a total of 283 individuals (47.1% men) aged 18-87 years old were included in the analysis. The participants were examined at the University Hospital of Augsburg, Southern Germany. Fatigue was assessed using the Fatigue Assessment Scale (FAS). Levels of anti-SARS-CoV2-spike IgG antibodies were measured by an enzyme-linked immunosorbent assay (ELISA), and for exploration of the SARS-CoV2-specific T-cell response, ex vivo ELISpot/FLUOROspot assays were conducted using an interferon-γ (IFN-γ) and interleukin-2 (IL-2) SARS-CoV-iSpot kit. Results Women more significantly suffered from post-COVID-19 fatigue in comparison to men (44.9% versus 24.8%, p=0.0005). Females but not males with fatigue showed a significantly lower number of T-cells producing IFN-γ, IL-2 or both IL-2 and IFNγ in comparison with females without fatigue. In both sexes, serum levels of anti-SARS-CoV2-spike IgG antibodies did not differ significantly between participants with or without fatigue. While there were no significant differences in serum IL-6 levels in men with and without fatigue, the levels differed significantly in women. Conclusions Development of fatigue after acute COVID-19 disease treated outpatient might be associated with SARS-CoV-2-specific T-cell responses and low-grade chronic inflammation in women, but not men.